Molecular weight analysis of starches: which technique? - Harding, Stephen E.; Adams, Gary G.; Gillis, Richard B. (Wiley-VCH Verlag, 2016)
A number of methods are available to researchers for estimating molecular weights (molar masses) and molecular weight distributions of starches − or those in solution, using an appropriate solvent/solubilisation protocol. We outline the methods available and assess their relative merits and limitations. We focus on size-exclusion chromatography or field flow fractionation coupled to multi-angle light scattering, viscometry, and sedimentation velocity and sedimentation equilibrium in the analytical ultracentrifuge.